An integrative review of stakeholder views on Advance Care Directives (ACD): Barriers and facilitators to initiation, documentation, storage, and implementation. Issue 6 (June 2019) - Hemsley, Bronwyn; Meredith, Jacqueline; Bryant, Lucy; Wilson, Nathan J.; Higgins, Isabel; Georgiou, Andrew; Hill, Sophie; Balandin, Susan; McCarthy, Shaun
Highlights: Advance Care Planning and Advance Care Directives are important elements of end-of-life care planning. Health professionals might avoid discussion of Advance Care Directives and need guidance on initiating the conversation. An online storage option for Advance Care Directives might help to facilitated documentation. Further research is needed on implementation of Advanced Care Directives. Abstract: Objective: To examine the views and experiences of patients and their health care providers on developing advance care planning (ACP) and advance care directives (ACD); and determine barriers and facilitators to ACD development, storage, and use, including implications for people with communication disability. Method: An integrative review of 93 studies, analysed according to their content themes. Results: Content themes encapsulated the initiation, documentation, and implementation stages of ACP/ACD. Lack of guidance for initiating and supporting ACP/ACD impedes discussions, and both patients and healthcare providers avoid discussions owing to fear of dying and reluctance to think about end-of-life. Conclusions: There are several barriers and facilitators to the initiation of ACP discussions, documentation and implementation of ACD, and little research exploring the views of legal professionals on the development, storage, or use of ACP documents. Further research is needed to explore the timing and responsibility of both legal and health professionals in initiating and supporting ACP discussions. Practice Implications: It is important for healthcare providers to raise ACP discussions regularly so that patients have time to make informed advance care decisions. Storage of the document in an electronic health record might facilitate better access to and implementation of patients' end-of-life care decisions.